2021
DOI: 10.1111/hdi.12927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemodialysis access surveillance on reducing risk of hemodialysis access thrombosis: A meta‐analysis of randomized studies

Abstract: Introduction Vascular access thrombosis remains the Achilles Heel for many a hemodialysis patient. We performed a systematic review and meta‐analysis to assess the impact of monitoring vascular access blood flow on prediction and prevention of vascular access thrombosis. We hypothesized that monitoring vascular access blood flow has a pivotal role in lowering the risk of thrombosis and subsequent access failure. Methodology We conducted a systematic review in PubMed and EMBASE databases to identify randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…4 The latest randomized clinical trials and subsequent metaanalysis have revealed that VA flow monitoring has a positive predictive value to identify VA at risk of developing thrombosis. [5][6][7][8] Although VA duplex ultrasonography (DUS) is currently a method that is acquiring a greater relevance, it is not available in all centers and there are several disadvantages dependant on the operator's experience and accuracy. 9 Classic ultrasound dilution (UD) methods allow detection of AVF risk through a simple method with computer-calculated results.…”
Section: Introductionmentioning
confidence: 99%
“…4 The latest randomized clinical trials and subsequent metaanalysis have revealed that VA flow monitoring has a positive predictive value to identify VA at risk of developing thrombosis. [5][6][7][8] Although VA duplex ultrasonography (DUS) is currently a method that is acquiring a greater relevance, it is not available in all centers and there are several disadvantages dependant on the operator's experience and accuracy. 9 Classic ultrasound dilution (UD) methods allow detection of AVF risk through a simple method with computer-calculated results.…”
Section: Introductionmentioning
confidence: 99%